PERSEPSI MASYARAKAT TERHADAP KEGIATAN EKOWISATA BAHARI DI PANTAI MUTIARA INDAH KECAMATAN MUARA BADAK KABUPATEN KUTAI KARTANEGARA. - Indar sari; Erwiantono; Gusti Haqiqiansyah (2339-1324, 2022)
This study aimed at knowing the public perception towards the development of marine ecotourism activities in Mutiara Indah beach based on the indicators referred by the Ministry of Tourism collaborating with WWF Indonesia. This study was conducted for 13 months, starting from January 2020 to March 2021. The sampling method was a case study with a total sample of 25 respondents. The analysis method was purposive sampling analysis. The result of this study showed that, in general, the people had a positive perception of 91.02% against the management continuity of marine ecotourism in Mutiara Indah beach, Tanjung Limau village. The public perception towards the ecotourism continuity from the aspect of the economy, social, and environment was in the high criteria of 100%, indicating strongly positive. The public perception towards the public institution development was at the high criteria of 100%, indicating strongly positive. The public perception towards a public-based economy was in the moderate criteria of 76%, indicating fairly positive. The public perception towards the educational principles was in the moderate criteria of 76%, indicating fairly positive. Meanwhile, the public perception towards the development and the implementation of site planning and framework for the ecotourism location management was in the positive criteria of 80%, indicating positive. Keywords: Public Perception, Ecotourism Manager, Tourist.